Childhood obesity and environmental pollutants: a dual relationship - Iughetti, Lorenzo; Lucaccioni, Laura; Predieri, Barbara (Acta Biomedica Atenei Parmensis, 2015)
The rise in obesity rates is an alarming global health concern. Despite obesity is mainly due to an unbalanced energy intake and expenditure, several recent studies suggest that it could be a consequence of exposure during critical developmental windows to environmental chemicals disrupting endocrine functions. This suggests that a shift is occurring in the human body pathways used to integrate changing nutritional and environmental variables and to maintain metabolic balance and body weight. This review highlights the role of pesticides, in particular endocrine disrupter ones, on obesity pathogenesis in childhood and summarizes the current under-standing of the major environmental influences on pediatric obesity. (www.actabiomedica.it)